Seeds and plantlets of Myrciaria dubia "camu-camu": biometry, germination, and initial growth - Medina Bardales, Anderson E. (2014)
The objectives were to determine seed biometrics, recording cellular respiration in the imbibition process, evaluate the effect of inducing chemicals in germination and early growth analysis. Cellular respiration during imbibition was measured by reduction of methylene blue and Janus Green B. The inductor effect of five chemical compounds in germination was evaluated. Initial growth was recorded by stereoscopic. Results showed that the seeds have an average weight of 520 ± 172 mg, length of 13.50 ± 1.76 mm, width of 10.61 ± 1.14 mm, and thickness of 4.68 ± 0 62 mm. These variables showed significant correlations (r of 0.494 to 0.897 and p90% and 65% respectively. Seedling initial growth consisted of six stages and occurred over a period of 22 days after radicle emergence. In conclusion, M. dubia seeds show wide variation in their biometrics (weight, length, width and thickness), but show significant correlations with each other. Likewise, seeds are metabolically active in imbibition process, and germination is induced by sodium nitrite and potassium cyanide. Furthermore, seedling initial growth to occur over a period of 22 days after emergence of the radicle and consists of six distinct stages.